Nominal Ellipsis in English & Arabic and its Influence on the Translation of the Meanings of Some Selected Qurànic Verses ( A Contrastive study ): هدى فالح حسن & جمانة شكيب محمد (Journal of the College of Education for Women, 2019)
Nominal ellipsis is a linguistic phenomenon found in English and Arabic .It isbased on leaving out a part of a nominal construction or more for the sake of goodstyle , compactness and connectedness .This phenomenon is found in the language ofthe Glorious Qur’an .The study in hand is concerned with how translators handletranslating Qur’anic verses which contain ellipted nouns , i ,e. , to what extent thetranslated Qur’anic verses are close to the original ones , and to what extent theirtranslations serve understanding the meanings of the glorious verses while at thesame time maintaining their beauty in style. The study aims at shedding light onnominal ellipsis in English and Arabic .The study undertaken here is hoped to besignificant in the field of contrastive studies and language universals. It is also hopedto be of value in the field of translating the meanings of the glorious Qur’an inparticular and translation in general .The study is concerned with nominal ellipsis in Standard English and StandardArabic. The translations studied are Ali (1934) and Al- Hilâli and Khân (1413 A.H.) .